1999
DOI: 10.1021/jf980829l
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone Treatment on Postharvest Strawberry Quality

Abstract: The effect of ozone treatment on the postharvest quality of strawberry was evaluated. Strawberry fruits (Fragaria x ananassa Duch. cv. Camarosa) were stored at 2 degrees C in an atmosphere containing ozone (0.35 ppm). After 3 days at 2 degrees C, fruits were moved to 20 degrees C to mimic retail conditions (shelf life). The changes in several quality parameters such as fungal decay, color, sugar and acids distribution, and aroma were evaluated during the strawberries' shelf life. Ozone treatment was ineffectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(127 citation statements)
references
References 14 publications
9
112
0
6
Order By: Relevance
“…2 ppm ozonization recorded minimum browning with scores of 3.86 and 4.10 and the highest mean score of 4.90 and 5.00 for control (without any pre-treatment) after 4 th and 5 th day of storage respectively (Table 1). Similar results were reported by Barth et al, (1995) in blackberries and Perez et al, (1999) in strawberries.…”
Section: Resultssupporting
confidence: 90%
“…2 ppm ozonization recorded minimum browning with scores of 3.86 and 4.10 and the highest mean score of 4.90 and 5.00 for control (without any pre-treatment) after 4 th and 5 th day of storage respectively (Table 1). Similar results were reported by Barth et al, (1995) in blackberries and Perez et al, (1999) in strawberries.…”
Section: Resultssupporting
confidence: 90%
“…As a very reactive oxidizing agent, O 3 has proved effective against a broad spectrum of living organisms and chemicals. It kills bacteria, fungi, yeasts, viruses and protozoa [17,18,[22][23][24][25][26][27][28] storage pests, such as insects & mites. It also has the potential to degrade mycotoxins, pesticides and toxic chemical wastes [2, 7-9, 26, 29-34].…”
Section: Ozone Gasmentioning
confidence: 99%
“…Oztekin et al (2006) reported reduction of microorganism counts on dried figs at a minimum of 3 hours treatment at 5 mg/l of O 3 , decreasing the total yeast/fungi counts of 72%. In post-harvest of strawberry, Perez et al (1999) observed fungal decay after 4 days of storage under ozonation. Lanita & da Silva (2008) utilized O 3 for controlling fungi in Parmesan cheese maturation (total fungi count reduced from 10 to 3.7 cfu/plate).…”
Section: Introductionmentioning
confidence: 97%
“…It can be applied to food as a gas or dissolved in water. The main purposes of O 3 application at the post-harvest stage are as follows: inactivation of bacterial growth (Sharma et al, 2002), prevention of fungal decay (Perez et al, 1999;Olmez et al, 2009) destruction of pesticides and chemical residues (Hwang et al, 2001) and control of storage pests (Kells et al, 2001). The attractive aspect of O 3 is that it decomposes rapidly (half-life of 20-50 min) to molecular oxygen without leaving a residue (Kells et al, 2001).…”
Section: Introductionmentioning
confidence: 99%